Perceived Stress Among Post Graduate Students And Its Association With Academic Performance - et. al., Raghunath Reddy Challa; (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
College days are said to be the most cherished and golden days in a person’s life. It is in college that a student enjoys the vibrant college environment, the circle of friends, numerous academic and other extra co-curricular activities, which enhance their skills and also boost up their confidence. This attribute is slowly dying away with the invasion of stress in the life of a student. The increase in stress levels has dire consequences. These days, college students are exposed to chronic stress and can suffer from several long-term side effects, like developing insulin-dependent diabetes. Apart from this, a matter of grave concern is the rise in suicide rates amongst college-going students. As described by American College Health Association, statistics published in Psychology Today show that the suicide rates in students have increased to threefold when compared to what it was in 1950. Therefore, in this study the researcher has tried to know the factors which influence the performance of the students. The research has collected the primary data with a sample of 160, who are the post graduate students of arts and science from Hyderabad. The sample has taken with convenience sampling.